Ball-milled modified graphite-phase carbon nitride photocatalytic antibacterial film as well as preparation method and application thereof

The particle size of graphite phase carbon nitride is adjusted through ball milling technology and loaded into the polyvinyl alcohol film, which solves the problem of poor antibacterial function of existing food plastic wrap, and improves the photocatalytic sterilization performance and fruit preservation effect.

CN119264483APending Publication Date: 2025-01-07YANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411361291.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing food plastic wrap lacks antibacterial function, and the graphite phase carbon nitride photocatalyst has too large particle size, small specific surface area, and serious photogenerated carrier recombination, resulting in low efficiency in actual applications and difficult to achieve long-term antibacterial effects.

Method used

The particle size of graphite phase carbon nitride was adjusted through ball milling technology, and reduced from 139.23 to 155.30 μm to 3.51 to 4.13 μm, and loaded it into a polyvinyl alcohol (PVA) film. Combined with dry and wet ball milling methods, we prepared Extrusion-milled modified graphite phase carbon nitride photocatalytic antibacterial film.

Benefits of technology

Improve the specific surface area and redox capacity of graphite phase carbon nitride, enhance the photocatalytic bactericidal properties, achieve efficient killing of Acinetobacter baumannier, Staphylococcus aureus and E. coli, and show it in fruit preservation Good fresh preservation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264483A_ABST
    Figure CN119264483A_ABST
Patent Text Reader

Abstract

The invention discloses a ball-milling modified graphite phase carbon nitride photocatalytic antibacterial film and a preparation method and application thereof in the field of antibacterial materials. The ball-milling modified graphite phase carbon nitride photocatalytic antibacterial film is prepared by taking graphite phase carbon nitride (g-C3N4) as an antibacterial agent and polyvinyl alcohol as a film forming substrate in a curtain coating plate coating manner. According to the invention, ball-milled and modified carbon nitride is selected as a photocatalytic antibacterial agent and is successfully loaded on the polyvinyl alcohol film, so that the photocatalytic antibacterial activity is enhanced, and the problem that a powder catalyst is difficult to apply practically is solved. The ball-milling technology and the casting plate coating film preparation process adopted by the invention are relatively simple to operate, and the prepared ball-milling modified graphite phase carbon nitride photocatalytic antibacterial film has good visible light response characteristic and excellent antibacterial performance, is safe, non-toxic, green and environment-friendly, and has wide application prospects. Wide application prospects are realized in the fields of photocatalytic sterilization, food, fruit and vegetable preservation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photocatalytic materials and fresh-keeping materials, and in particular to a ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film, a preparation method thereof and use thereof. Background Art

[0002] In recent years, the research on food cling film has been rapidly advancing, and its functionality and safety are one of the hot issues studied by many scholars. At present, the common food cling film (polyethylene, polyvinyl chloride and polyvinylidene chloride cling film) that we can see on the market does not have antibacterial function, and the safety of the only silver ion antibacterial cling film is difficult to control. Therefore, it is of great significance to study antibacterial cling film that is harmless to the human body and has excellent antibacterial properties.

[0003] There are many types of film-forming matrix materials, including some polysaccharides, proteins, lipids and high molecular polymers. Among them, polyvinyl alcohol (PVA) is a fibrous powder that is white, odorless and tasteless, and can be completely biodegraded. At the same time, it also has good emulsification, water solubility, oil and solvent resistance, and is easy to form a film. It has no toxic side effects on the human body. It is a good film-forming material and is green and environmentally friendly.

[0004] As for the supported photocatalytic antibacterial agents, titanium dioxide (TiO 2 )、ZnO、Graphite Carbon Nitride (gC 3 N 4 ) etc. Among them, gC 3 N 4 It is a non-metallic two-dimensional semiconductor material. Its advantage of not containing metal is that it is conducive to its application in the field of food antibacterial preservation. It also has good thermal stability, chemical stability and biocompatibility, and is environmentally friendly and has no secondary pollution. 2 and ZnO, gC 3 N 4 It has the characteristic of visible light response. In addition, gC 3 N 4 The synthesis method is relatively simple, and the raw materials used are relatively cheap, but the direct synthesis of gC 3 N 4Most photocatalysts are in the form of hard blocks, with problems such as small specific surface area, serious recombination of photogenerated carriers, low quantum efficiency, and difficulty in realizing practical industrial applications. Therefore, it is necessary to improve the photocatalytic performance of the catalyst through various means. Among them, size control is one of the modification strategies. However, in the prior art, there is no case of directly loading small-particle carbon nitride onto a membrane. Therefore, it is a technical problem that needs to be solved at present to explore the optimal ball milling parameters of carbon nitride in the laboratory, and then screen out the optimal size and optimal addition amount of ball-milled carbon nitride loaded on the membrane. Summary of the invention

[0005] The purpose of the present invention is to provide a ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film, a preparation method and use thereof, so as to overcome the problems in the prior art that ordinary cling film has a short shelf life, the bulk carbon nitride has poor photocatalytic activity and the powder catalyst is not conducive to practical application. The preparation process is simple, and the prepared film can achieve long-term antibacterial effect, and has good application prospects in the fields of photocatalytic antibacterial and food preservation.

[0006] To this end, the present invention provides a method for preparing a ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film, comprising the following steps:

[0007] (1) Preparation of bulk gC using melamine as a precursor 3 N 4 ;

[0008] (2) For bulk phase gC 3 N 4 Ball milling was performed to prepare gC with a particle size of 139.23 to 155.30 μm by dry ball milling. 3 N 4 Then, gC with a size of 3.51 to 4.13 μm was prepared by wet ball milling with anhydrous ethanol. 3 N 4 ;

[0009] (3) gC prepared in step (2) 3 N 4 Ultrasonic dispersion in anhydrous ethanol, then under the condition of heating in a water bath at 60-80°C, a 10% polyvinyl alcohol (PVA) aqueous solution, glycerol and gC dispersed in anhydrous ethanol were mixed and stirred. 3 N 4 After mixing and stirring to evaporate the ethanol, a membrane liquid is obtained, in which the degree of polymerization of the PVA used is 1700 and the degree of alcoholysis is 99%; after ultrasonic degassing, the membrane liquid is poured onto the surface of a clean glass plate, and allowed to stand and dry to obtain a ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film.

[0010] Furthermore, in step (3), the volume ratio of the PVA aqueous solution to glycerol is 10:(0.5-0.7), and the volume ratio of the PVA aqueous solution to gC 3 N 4 The mass ratio is 10:(0.2~0.4).

[0011] Furthermore, in step (3), gC 3 N 4 Before adding into the mixed solution of PVA aqueous solution and glycerol, it is first ultrasonically dispersed in 10 to 30 times the weight of anhydrous ethanol for 25 to 35 minutes.

[0012] Further, in step (1), the bulk phase gC 3 N 4 During the preparation, melamine is placed in an alumina crucible, heated to 500-600°C at a rate of 4.5-5.5°C / min in a muffle furnace, kept warm for 3.5-4.5 hours, and cooled to room temperature to obtain blocky gC 3 N 4 , and then use a mortar to grind gC 3 N 4 Grind into powder, pass through 70 mesh sieve, and obtain bulk phase gC 3 N 4 .

[0013] Further, in step (2), the dry ball milling phase gC 3 N 4 The specific steps are as follows: put the bulk phase gC into each of the two agate jars of the planetary ball mill. 3 N 4 After the agate cover with a rubber ring is put on, the agate jar is placed in the ball mill and fixed, the speed and ball milling time are set, and the forward and reverse rotations are alternately operated. The interval between each alternating operation is 30 seconds. After the ball mill is stopped, the powder attached to the inner wall of the jar is collected and scraped off to obtain the gC of dry ball milling. 3 N 4 ; Wet ball milling phase gC 3 N 4 The specific steps are as follows: weigh the gC 3 N 4 Add the agate balls into the agate tank of the planetary ball mill, control the ball-to-material weight ratio to 10:1, and then add gC 3 N 4The weight of anhydrous ethanol is 20 to 40 times, and the agate cover with a rubber ring is placed. The agate jar is placed in the ball mill and fixed. The speed and ball milling time are set, and the forward and reverse rotations are alternately operated. The time interval of each alternating operation is 30 seconds. After the set program of the ball mill stops, the agate jar is taken out and anhydrous ethanol is added to it to wash the inner wall of the jar and the agate balls. The obtained mixed liquid is centrifuged and the obtained solid is placed in an oven at 55 to 65°C for 6 to 12 hours to obtain gC 3 N 4 .

[0014] The ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film prepared by the above method can be used for photocatalytic sterilization. The target bacteria to be killed are at least one of Acinetobacter baumannii (AB), Staphylococcus aureus (SA) and Escherichia coli (E.coli).

[0015] The ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film prepared by the method can be made into a fruit preservative film for fruit preservation.

[0016] The ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film of the present invention is prepared by using ball-milled modified graphite phase carbon nitride as an antibacterial agent and polyvinyl alcohol as a film-forming matrix through a tape-cast coating method. Beneficial effects of the present invention:

[0017] (1) The ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film prepared by the present invention combines the photocatalyst and the film material, uses graphite phase carbon nitride as the antibacterial agent and polyvinyl alcohol as the film-forming substrate, and solves the problem that the powder catalyst is difficult to realize practical application. The ball milling and tape casting coating methods adopted are safe and controllable, simple to operate, and cost-effective, providing a certain reference for the production of antibacterial films.

[0018] (2) The ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film prepared by the present invention is subjected to the bulk gC 3 N 4 Ball milling gradually reduces the particle size and increases the bandgap, which increases the bulk gC 3 N 4 The specific surface area of ​​gC increases the active sites and enhances the redox capacity, thereby improving the photocatalytic bactericidal performance. 3 N 4 The optimal size and optimal addition amount.

[0019] (3) The ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film prepared by the present invention is safe, non-toxic, green and environmentally friendly, and has excellent antibacterial properties. The fruit preservation experiment verifies that the photocatalytic antibacterial film has a certain market prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 : Actual pictures of carbon nitride of different sizes and film formation prepared based on Example 1; in the figure, (a) to (e) correspond to gC 3 N 4 , bgC 3 N 4 (1) bgC 3 N 4 (2) bgC 3 N 4 (3) bgC 3 N 4 (4), where (f) to (j) correspond to gC 3 N 4 / PVA, bgC 3 N 4 (1) / PVA, bgC 3 N 4 (2) / PVA, bgC 3 N 4 (3) / PVA, bgC 3 N 4 (4) / PVA film.

[0021] Figure 2 : The particle size range of carbon nitride of different sizes obtained in Example 1 and measured by using Bettersize 2600 laser particle size distribution analyzer (dry method).

[0022] Figure 3 : Scanning electron microscope images of carbon nitride of different sizes (a) to (e) and thin films made from (f) to (j) obtained in Example 1.

[0023] Figure 4 : Transmission electron microscope images of carbon nitride of different sizes (a) to (e) prepared based on Example 1.

[0024] Figure 5 : (a) UV-visible diffuse reflectance spectra and (b) UV band gap diagrams of carbon nitrides of different sizes prepared in Example 1.

[0025] Figure 6 : Based on bgC prepared in Example 1 3 N 4 (4) Pure PVA film, bgC 3 N 4 (a) XRD spectrum and (b) IR spectrum of (4) / PVA film.

[0026] Figure 7: The photocatalytic sterilization experiment effect diagram based on Example 2 using ball-milled modified graphite phase carbon nitride photocatalytic antibacterial films of different sizes.

[0027] Figure 8 : The photocatalytic sterilization experiment effect diagram of SA and E.coli using ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film based on Example 2.

[0028] Fig. 9 : The effect diagram of the fruit preservation experiment based on Example 3 on the ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0030] Example 1

[0031] The present invention uses graphite phase carbon nitride as an antibacterial agent and polyvinyl alcohol as a film-forming substrate, and adopts a tape-casting coating method to prepare a ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film, which specifically includes the following steps:

[0032] 1. Body phase gC 3 N 4 Preparation

[0033] 20 g of melamine was placed in a 30 mL alumina crucible with a lid, heated to 550 °C in a muffle furnace at a rate of 5 °C / min and kept at this temperature for 4 h to obtain blocky gC 3 N 4 Next, put the large piece of gC 3 N 4 The mixture was cooled to room temperature and ground into powder using a mortar. The powder was then sieved (70 mesh) to obtain bulk carbon nitride powder without ball milling treatment, which was directly named gC 3 N 4 .

[0034] 2. Dry ball milling phase gC 3 N 4 : Place 1 g of the prepared bulk phase gC in each of the two agate jars of the planetary ball mill. 3 N 4 , control the ball-to-material mass ratio to 10:1. Cover the agate cover with a rubber ring, place the agate jar in the ball mill and fix it, ensure that the total mass of the symmetrically placed agate jars is similar, set the speed to 350rpm, the ball milling time to 10min and alternate forward and reverse rotations, each alternating operation interval is 30s, after the ball mill setting program stops, collect and scrape off the powder attached to the inner wall of the jar to obtain gC of dry ball milling. 3 N 4Here, the gC corresponding to the ball milling speed of 350 rpm and the ball milling time of 10 min is 3 N 4 , named bgC 3 N 4 (1). Similarly, by changing the ball milling speed and ball milling time, gC of different sizes were obtained. 3 N 4 For example, the gC corresponding to the ball milling speed of 550 rpm and the ball milling time of 10 min is 3 N 4 , named bgC 3 N 4 (2) gC corresponding to a ball milling speed of 550 rpm and a ball milling time of 30 min 3 N 4 , named bgC 3 N 4 (3).

[0035] Wet ball milling phase gC 3 N 4 : In order to obtain smaller carbon nitride, 1g of bulk phase gC is weighed 3 N 4 Place it in two clean agate ball mill jars, add 30 mL of anhydrous ethanol and 10 g of agate balls to each of them, cover it with an agate cover with a rubber ring, place the agate jar in the ball mill and fix it, set the speed to 550 rpm, the ball milling time to 16 h, and alternately run the forward and reverse rotations for 30 min each, and the time interval between each alternating operation is 30 s. After the program set by the ball mill stops, take out the agate jar and add an appropriate amount of anhydrous ethanol to rinse the inner wall of the jar and the agate balls. Centrifuge the obtained mixed solution, and place the obtained lower layer of solid in a 60 ° C oven for drying for 12 h. The obtained powder is gC modified by wet ball milling with ethanol. 3 N 4 Here, we name it bgC 3 N 4 (4).

[0036] 3. Preparation of photocatalytic antibacterial films of graphite carbon nitride of different sizes modified by ball milling

[0037] (1) The graphite phase carbon nitride photocatalytic antibacterial film was prepared by tape casting. First, 180 mL of deionized water was measured in a round-bottom flask, and a rotor was placed. Then, 20 g of polyvinyl alcohol (PVA, degree of polymerization of 1700, degree of alcoholysis of 99%) was accurately weighed and added to the round-bottom flask, and the stopper was covered. After the constant temperature heating magnetic stirrer reached 95°C, the round-bottom flask was placed and magnetically stirred for 5 h to ensure that the PVA was fully dissolved, and a PVA aqueous solution with a mass concentration of 10% was prepared. The solution was allowed to stand, cooled to room temperature, and then stored for later use.

[0038] (2) In order to ensure gC 3 N 4 Fully dispersed in the membrane solution, weighed 0.2g of gC of different sizes prepared in step 1 respectively. 3 N 4 , bgC 3 N 4 (1) bgC 3 N 4 (2) bgC 3 N 4 (3) and bgC 3 N 4 (4), each dispersed in 5 mL of anhydrous ethanol and ultrasonicated for 30 minutes. Then, use a syringe without a needle to extract 10 mL (about 10 g) of 10% PVA aqueous solution and 0.5 mL of glycerol and add them to a beaker, then pour in the carbon nitride-anhydrous ethanol dispersion after the ultrasonication, mix and stir in a water bath at a temperature of 60-80 ° C (to evaporate the ethanol) to obtain a membrane liquid. Ultrasonicate for 10 minutes for degassing, then use a syringe to draw 2 mL of the membrane liquid and evenly cast it on a glass disc with a diameter of 8.5 cm, let it stand and dry for 12 hours to obtain gC 3 N 4 / PVA, bgC 3 N 4 (1) / PVA, bgC 3 N 4 (2) / PVA, bgC 3 N 4 (3) / PVA and bgC 3 N 4 (4) / PVA film.

[0039] Comparative Example:

[0040] Preparation of pure PVA film

[0041] In the film solution containing 10 mL of 10% PVA aqueous solution and 0.5 mL of glycerol, no carbon nitride-anhydrous ethanol dispersion was added, and the bubbles were removed by ultrasonication for 10 minutes after heating and stirring. 2 mL of the film solution was drawn with a syringe and evenly cast on a glass disc with a diameter of 8.5 cm. After standing and drying for 12 hours, a pure PVA film was obtained.

[0042] The prepared carbon nitride of different sizes and the actual pictures of the film are as follows: Figure 1 The specific particle size results of carbon nitride samples are shown in Figure 2 Its morphology is shown in Figure 3 , 4 Its photoresponse range and energy band structure are shown in Figure 5 Its structure is as shown in Figure 6 shown.

[0043] Figure 1 The actual pictures of carbon nitride of different sizes and film formation prepared in Example 1; in the figure, (a) to (e) correspond to gC 3 N 4 , bgC 3 N 4 (1) bgC 3 N 4 (2) bgC 3 N 4 (3) bgC 3 N 4 (4), (f) to (j) correspond to gC 3 N 4 / PVA, bgC 3 N 4 (1) / PVA, bgC 3 N 4 (2) / PVA, bgC 3 N 4 (3) / PVA, bgC 3 N 4 (4) / PVA film.

[0044] Figure 2 is the particle size range of carbon nitride of different sizes obtained in Example 1 and measured by using Bettersize 2600 laser particle size distribution analyzer (dry method); in the figure, as the ball milling speed and time increase, gC 3 N 4 , bgC 3 N 4 (1) bgC 3 N 4 (2) bgC 3 N4 (3) bgC 3 N 4 The particle size of (4) gradually decreased from the original 139.23-155.30 μm to 3.51-4.13 μm, and the ball milling effect was significant.

[0045] Figure 3 The scanning electron microscope images of the carbon nitride films of different sizes (a) to (e) and (f) to (j) prepared in Example 1; in the figure, under the same scale, gC 3 N 4 , bgC 3 N 4 (1) bgC 3 N 4 (2) bgC 3 N 4 (3) bgC 3 N 4 (4) The SEM and particle size test results are consistent, the size gradually decreases, the specific surface area increases, and after being loaded on PVA, it becomes more and more uniform and more active sites are exposed per unit area.

[0046] Figure 4 The carbon nitrides of different sizes (a) to (e) are obtained based on Example 1. (a) is a TEM image of bulk carbon nitride material. It can be seen that due to the thick sample, it is difficult for electrons to penetrate the sample, so a large number of black areas appear in the field of view, and the edges of different depths indicate that the carbon nitride is composed of many small-sized layers stacked. However, after different degrees of ball milling, the contrast of the sample becomes lower, and the overall structure gradually presents an obvious flaky structure, indicating that the thickness of the carbon nitride becomes thinner after ball milling. At the same time, ball milling realizes the interlayer exfoliation of carbon nitride and will also destroy its two-dimensional layers to a certain extent.

[0047] Figure 5 The following are (a) UV-visible diffuse reflectance spectra and (b) UV band gap diagrams of carbon nitrides of different sizes prepared in Example 1; the results show that as the size of carbon nitride decreases, its absorption edge gradually blue-shifts and eventually moves from 490nm of the original carbon nitride to 450nm. This may be due to the reduction of the size and thickness of the carbon nitride sample, which enhances the quantum confinement effect, and its conduction band position and valence band position move in opposite directions, thereby enhancing the oxidation ability of holes and the reduction ability of electrons. By calculating gC 3 N 4 , bgC 3 N 4 (1) bgC 3 N 4 (2) bgC3 N 4 (3) bgC 3 N 4 The band gap widths of (4) are 2.38eV, 2.44eV, 2.48eV, 2.53eV, and 2.62eV, respectively. It can be seen that the band gap width of carbon nitride after ball milling modification becomes larger, which enhances the redox ability to a certain extent, which is beneficial to the improvement of photocatalytic bactericidal performance.

[0048] Figure 6 bgC prepared based on Example 1 3 N 4 (4) Pure PVA film, bgC 3 N 4 (a) XRD spectrum and (b) IR spectrum of (4) / PVA film; in the figure, in bgC 3 N 4 (4) / The XRD pattern of PVA shows bgC 3 N 4 (4) The characteristic peaks of the powder, and bgC 3 N 4 (4) and bgC 3 N 4 (4) / The IR spectrum of PVA is at 806 cm -1 There is a characteristic absorption peak at each location, which is similar to bgC 3 N 4 (4) The NCN triazine unit in the structure is related, indicating that carbon nitride is successfully loaded on PVA.

[0049] Example 2

[0050] Using gC prepared in Example 1 3 N 4 / PVA, bgC 3 N 4 (1) / PVA, bgC 3 N 4 (2) / PVA, bgC 3 N 4 (3) / PVA, bgC 3 N 4(4) / PVA photocatalytic antibacterial film was used for photocatalytic oxidation sterilization experiment, and the photocatalytic sterilization efficiency of the photocatalytic antibacterial film was determined by killing Acinetobacter baumannii (AB), Staphylococcus aureus (SA) and Escherichia coli (E. coli). Among them, AB is a multidrug-resistant pathogen that is currently harmful to human society. It has strong vitality and is one of the main pathogens of aquaculture and hospital infections. SA and E. coli are one of the most representative Gram-positive and Gram-negative bacteria, and are also the target bacteria specified in the national standards for antibacterial films. Therefore, it is of great significance that we choose these three bacteria to kill. The specific steps are as follows:

[0051] 1. Bacteria recovery

[0052] (1) Take out the culture from a refrigerator at -60°C;

[0053] (2) Thaw the bacterial strain on ice, pipette a small amount (100 μL) into 5 mL of liquid culture medium, and culture at 37°C in a shaking incubator overnight.

[0054] 2. Take a single colony

[0055] Dip the inoculation loop into the cultured bacterial solution in step 1, draw three zones on the plate to isolate single colonies, and then place the plate with three zones in a 37°C constant temperature incubator overnight. Then use a pipette to pick up the single bacteria on the plate, add 5mL of liquid culture medium, and culture in a shaking incubator at 37°C overnight. On the second day, obtain the single colony culture of the target strain, and store it at 4°C for use. This process propagates the target strain, avoids the mixing of other bacteria, and can be stored for 7 to 10 days.

[0056] 3. Shake OD

[0057] The purpose of this step is to obtain bacteria in the logarithmic growth phase. It is usually carried out on the day of the photocatalytic experiment. If the bacteria are left to age and die and toxins accumulate on the next day, this will theoretically affect the experimental results. The specific steps are to take 200 μL of a single colony of bacteria and add it to 5 mL of liquid culture medium. Incubate at 37°C in a shaking incubator until the OD value is measured by a UV-visible spectrophotometer. 600 The value of is 0.5, and the bacterial solution in the logarithmic growth phase is obtained, and its concentration is about 10 8 CFU / mL.

[0058] 4. Photocatalytic sterilization experiment

[0059] A 300W xenon lamp was used as the light source for photocatalytic sterilization, and light waves below 400nm were filtered out. The visible light radiation intensity was adjusted to 100mW / cm by a high-brightness photoelectric power meter. 2 The utensils used in this experiment must be sterilized at 121℃ for 20 minutes and then sterilized by ultraviolet light for 30 minutes.

[0060] (1) Take 20 mL of PBS, a circular film with a diameter of 8.5 cm, and 400 μL of bacterial solution, mix them in a 9 cm glass culture dish, and turn on the light for the experiment.

[0061] (2) Take samples at 0, 20, 40, 60, 80, 100, and 120 minutes and count the points.

[0062] (3) Dilute the culture solution in a gradient of 10, 100, and 1000 times, then drop 10 μL of the diluted bacterial solution onto the prepared LB solid medium. Place the spotted plate in a constant temperature incubator at 37°C for 12 h, and count the number of colonies using the spot plate counting method.

[0063] (4) Under the same other experimental conditions, the photocatalytic antibacterial film was placed in the dark for control experiments and the photocatalyst-free control experiments were used as control experiments. All bactericidal experiments were carried out in an ice bath and repeated three times to avoid temperature interference with the reaction.

[0064] (5) After completion, all container waste that has come into contact with bacteria should be soaked in 84 disinfectant and then cleaned or discarded.

[0065] (6) The sterilization rate formula is:

[0066]

[0067] Where SR% is the killing rate of AB by ball-milled graphite phase carbon nitride photocatalytic antibacterial film, N 0 is the initial colony count (CFU) of AB, N t is AB (CFU) at time t. The bactericidal efficiency can also be more intuitively illustrated by taking the logarithm of the bacterial colony concentration.

[0068] Figure 7 In order to conduct photocatalytic sterilization experiments using ball-milled modified graphite phase carbon nitride photocatalytic antibacterial films of different sizes based on Example 2, the optimal size of carbon nitride powder was determined to be 3.51-4.13 μm by the sterilization rate of AB, corresponding to bgC 3 N 4 (4) Catalyst. Then, the PVA aqueous solution and bgC 3 N 4 The optimal mass ratio of (4) is 10:0.2, and the sterilization rate of AB can reach 99.99%, indicating that after deep ball milling, the specific surface area of ​​carbon nitride increases, the number of active sites increases, and the photocatalytic performance is improved.

[0069] Figure 8 Based on Example 2, the ball-milled bgC 3 N 4(4) / PVA photocatalytic antibacterial film was used to perform photocatalytic sterilization experiments on SA and E. coli. The bgC 3 N 4 The bactericidal rate of (4) / PVA photocatalytic antibacterial film against SA was 88.19%, and that against E. coli was 98.33%.

[0070] Example 3

[0071] The best performance bgC determined by the photocatalytic sterilization experiment of Example 2 using the film prepared in Example 1 3 N 4 (4) / PVA film was used to carry out a fruit preservation experiment. The degree of improvement in the preservation performance of the ball-milled graphite phase carbon nitride photocatalytic antibacterial film was determined by the preservation effect on strawberries.

[0072] According to the packaging characteristics of strawberries in the market, a double-layer film-wrapped experimental device was designed. First, five strawberries of the same size and freshness were selected. Secondly, a circular ordinary PE cling film with a diameter of 8.5 cm, an antibacterial cling film purchased on the market, a pure PVA film and bgC were selected. 3 N 4 (4) / Two pieces of PVA film were used, one was placed on the bottom of the strawberry, and the other was placed on top of the strawberry. A blank group without any treatment was used as a control. The outer layer was covered with a plastic culture dish to simulate the actual situation of fruit transportation. Finally, in the strawberry preservation experiment, photos of the strawberries in each culture dish were taken every 24 hours, and the preservation effect of the film was evaluated based on the degree of strawberry decay. The results are shown in the figure. Fig. 9 As shown in the figure, the strawberries all began to shrink to a certain extent from the third day, and bacteria began to multiply on the sixth day. The strawberries packed with ordinary PE plastic wrap rotted the most seriously. As the storage time increased, the degree of strawberry rot increased rapidly. On the ninth day, the strawberries all lost water seriously. 3 N 4 (4) / The deterioration degree of strawberries covered with PVA film and pure PVA film was much lower than that of the uncovered group, antibacterial cling film and ordinary PE cling film. After the 12th day, bgC 3 N 4 (4) / The strawberries packaged with PVA film had the lowest decay rate, which indicated that bgC 3 N 4 The addition of (4) greatly improved the antibacterial activity of the film.

[0073] In order to further illustrate the technical effects of the present invention, the present invention also provides more embodiments for effect comparison.

[0074] The following table lists the addition amount of 10% PVA aqueous solution in step 3, and changes in bgC 3 N 4 Examples 1, 4 to 8 show different mass ratios of bgC 3 N 4 (4) / Bacterial killing rate of PVA photocatalytic antibacterial film on AB.

[0075] Serial number PVA aqueous solution addition amount (g) Carbon nitride addition amount (g) Sterilization rate at 2h (%) Example 4 10 0.05 89.68 Example 5 10 0.1 98.81 Example 1 10 0.2 99.99 Example 6 10 0.4 99.97 Example 7 10 0.5 93.62 Example 8 10 0.6 Too thick and difficult to form film

[0076] The ball-milled modified carbon nitride is loaded on PVA as a photocatalytic antibacterial agent, which transforms the pure PVA film into a film with photocatalytic antibacterial activity, so the photocatalytic bactericidal performance is used as an evaluation index. As can be seen from the above table, when the mass ratio of PVA aqueous solution to carbon nitride is 10:0.2-0.4, the photocatalytic bactericidal performance of the photocatalytic antibacterial film is better.

[0077] Further, in step 3, the reason for adding glycerol is: PVA film is easy to crystallize under certain conditions, which reduces its physical properties and application value. In order to solve this problem, by adding an amount of plasticizer, the softness and toughness of film are increased, thereby improving and improving the physical and mechanical properties of film. Glycerol is a nontoxic triol organic compound with good moisture retention, lubricity and permeability. It is added in PVA as a plasticizer, can be inserted into the polymer molecular chain, and with numerous hydroxyl groups therein, hydrogen bonds are formed, effectively destroying the hydrogen bonds formed between the polymer molecular chains and in the molecule, so that the interaction between the polymer molecules and the molecule itself is greatly weakened, softening the rigid structure of the film, thereby improving the mechanical properties of the film. In addition, the glass transition temperature of the film can also be reduced, and the transparency of the film can also be improved to a certain extent.

[0078] The following table lists the addition amount of 10% PVA aqueous solution in step 3, with the amount of glycerol added being changed. 3 N 4 (4) / Tensile strength, elongation at break and transmittance of PVA films at 600 nm.

[0079]

[0080] As can be seen from the above table, with the increase of glycerol dosage, the tensile strength of the film gradually increases and then gradually decreases; the tensile strength of the film between 0.5mL and 0.7mL does not change much, showing a slow downward trend. In the process of increasing from 0.1mL to 0.5mL, the tensile strength of the film continues to increase, increasing by 31.6%. When the amount of glycerol added is greater than 0.7mL, the tensile strength decreases rapidly. The elongation at break of the film shows an increasing trend with the increase of glycerol addition. Basically, the more glycerol is added, the greater the elongation at break. It can be seen from the table that it has increased by 64.2%, a large increase. Therefore, while plasticizers increase the flexibility of the film, they often reduce the tensile strength of the film. The enhancement of the plasticizing effect is consistent with the further reduction of tensile strength. It can be seen that when determining the amount of glycerol added in the film, its effects on tensile strength and elongation at break should be comprehensively considered.

[0081] The transmittance of the film changes with the addition amount of plasticizer. The table above shows that when the addition amount of glycerol is 0.5mL, the transmittance of the film is the highest. When the amount of glycerol exceeds a certain value, it will not only cause wrinkles on the film surface, affecting the use effect, but also excessive glycerol molecules in the substrate will cause the glycerol on the surface of the composite film to overflow, affecting the sensory quality and storage.

[0082] Therefore, after comprehensively evaluating the tensile strength, elongation at break and transmittance of the film, when the volume ratio of PVA aqueous solution to glycerol is selected as 10:0.5-0.7, the mechanical properties and light transmittance of the photocatalytic antibacterial film are better.

[0083] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.

Claims

1. A method for preparing a ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film, characterized in that: The steps include: (1) Preparation of bulk g-C3N4 using melamine as a precursor; (2) ball milling the bulk g-C3N4, first using dry ball milling to prepare g-C3N4 with a particle size of 139.23-155.30 μm, and then using wet ball milling with anhydrous ethanol to prepare g-C3N4 with a particle size of 3.51-4.13 μm; (3) The g-C3N4 prepared in step (2) is ultrasonically dispersed in anhydrous ethanol, and then a 10% PVA aqueous solution, glycerol and g-C3N4 dispersed in anhydrous ethanol are mixed and stirred under a water bath heating condition at 60-80°C. After mixing and stirring to evaporate the ethanol, a membrane liquid is obtained. The degree of polymerization of the PVA used is 1700 and the degree of alcoholysis is 99%. After ultrasonic degassing, the membrane liquid is poured onto a clean glass plate surface and allowed to stand and dry to obtain a ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film.

2. The method for preparing the ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film according to claim 1, characterized in that: In step (3), the volume ratio of the PVA aqueous solution to glycerol is 10:(0.5-0.7), and the mass ratio of the PVA aqueous solution to g-C3N4 is 10:(0.2-0.4).

3. The method for preparing the ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film according to claim 1, characterized in that: In step (3), g-C3N4 is ultrasonically dispersed in 10 to 30 times the weight of anhydrous ethanol for 25 to 35 minutes before being added to the mixture of PVA aqueous solution and glycerol.

4. The method for preparing the ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film according to claim 1, characterized in that: In step (1), when preparing bulk g-C3N4, melamine is placed in an alumina crucible, heated to 500-600°C at a rate of 4.5-5.5°C / min in a muffle furnace, kept warm for 3.5-4.5 hours, and cooled to room temperature to obtain block g-C3N4. The g-C3N4 is then ground into powder using a mortar and sieved through a 70-mesh sieve to obtain bulk g-C3N4.

5. The method for preparing the ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film according to claim 1, characterized in that: In step (2), the specific steps of dry-milling the bulk phase g-C3N4 are as follows: placing bulk phase g-C3N4 and agate balls in two agate jars of a planetary ball mill, respectively, and controlling the ball-to-material weight ratio to be 10:1; after covering with an agate cover with a rubber ring, placing the agate jar in the ball mill and fixing it, setting the rotation speed and ball milling time, and running it alternately in forward and reverse directions, with an interval of 30 seconds for each alternating operation, and after the ball mill setting program stops, collecting and scraping off the powder attached to the inner wall of the jar to obtain dry-milled g-C3N4; The specific steps of wet ball milling bulk g-C3N4 are as follows: weigh the dry-milled g-C3N4 and agate balls and add them into the agate jar of the planetary ball mill, control the ball-to-material weight ratio to be 10:1, then add anhydrous ethanol 20 to 40 times the weight of the g-C3N4, and cover it with an agate lid with a rubber ring, place the agate jar in the ball mill and fix it, set the speed and ball milling time, and alternately run forward and reverse, with a time interval of 30 seconds for each alternating operation, after the set program of the ball mill stops, take out the agate jar and add anhydrous ethanol to it to rinse the inner wall of the jar and the agate balls, centrifuge the obtained mixed solution, and dry the obtained solid in an oven at 55 to 65°C for 6 to 12 hours to obtain wet-milled g-C3N4.

6. A ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film prepared according to the method of any one of claims 1 to 5.

7. The use of the ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film according to claim 6, characterized in that: Used for photocatalytic sterilization, the target bacteria is at least one of Acinetobacter baumannii, Staphylococcus aureus and Escherichia coli.

8. The use of the ball-milled modified graphite phase carbon nitride photocatalytic antibacterial film according to claim 6, characterized in that: Used to make fruit cling film for keeping fruits fresh.